DETECTION OF GAMMA RADIATION EFFECT INDUCED BY COBELT-60 ON ESCHERICHIA COLI CELLS - Al-Sudany, Ghusoon Ali Abdul Hasan; Majeed, Wasan Zuheir; Al-Aubeid, Hind Jabbar Abdul Rhman Akram (Al-Nahrain Journal of Science, 2010)
Effect of ionizing radiation induced by coblet-60 (Co-60) on Escherichia coli cells wasinvestigated. A cellular survival curve and mutant frequencies versus absorbed doses weredetermined. The results showed that the level of bacteria in survival curve decrease to (2) Log withgamma ray doses increase and D-value was equals (0.079) Gy. After irradiation the mutantfrequencies increased with doses increase, the greatest mutant frequency was 3.4 10-12 (1 mutationfor 0.29 1012 CFU for 150 g of rifampicin) induced by(1) Gy, while the smaller was 0.39 10-12(1 mutation for 3.41 1012 CFU for 150 g of rifampicin) induced by(0.1) Gy